Análise da aplicação da ferramenta de mapeamento do fluxo de valor estendido (E-VSM) na identificação de melhorias na cadeia de suprimentos: o caso de uma indústria de materiais elétricos. - Fontoura, Weber Chaves (2016)
The supply chain has been perceived in the past decade as a strategic area in Brazilian industrial organizations, which has led to a huge boost in the search for methods and tools that impact in reducing waste, increasing efficiency, reducing costs and mainly the level of service required by customers. To achieve this logistics performance level of many companies have resorted to lean tools presented in the West and developed from observations of the production methods used in Toyota Motor Company, however the implementation of this lean approach in the supply chain requires a complex network of information and vast connections between the participants in the chain. To see such complexity are necessary strategies and able to analyze the relationships within the plants of chain members as well as their relations firms tools; Extended map of the amount of flow (E-VSM) is a tool with the required capacity. This paper proposes, through a case study to examine the application of E-VSM tool in identifying waste in the supply chain of electrical materials industry located in Maracanaú municipality in Ceará. The company is family, multiprodutora and has no experience in the use of lean tools approach. Its organizational structure is not well defined, with management functions poorly defined and confusing. The industrial area is well divided into sectors, but abundant flows of divergent and parallel information. It has no computerized system of centralized control, with two banks of individual data with duplicate information in some cases. To achieve the study proposed a method of data collection and analysis, as well as unstructured interviews. Finally, the study showed that the E-VSM was able to identify waste in the company's supply chain even if this inexperienced and desaculturada the lean philosophy. In addition to identifying the tool was able to promote motivation, in part of the chain, for the implementation of the scenarios envisioned improvements. As it is understood that lean supply chain is a complex philosophy and dependent on systemic actions were corroborated some results presented in the literature: due to low trust between firms, the implementation of improvements scenarios in customers and suppliers could not It is perceived as a result, which limited some conclusions.